Characterization of Natural Cellulosic Fiber from Cereus Hildmannianus. Issue 3 (4th March 2021) - Subramanian, Senthil Ganesh; Rajkumar, R.; Ramkumar, T.
ABSTRACT: The research article aims to characterize the physicochemical, morphological, thermal and mechanical properties of novel Cereus Hildmannianus Fibers ( CHFs ) are reported for the first time in this work. The lower density (1.364 ± 0.026 g/cm 3 ) with high cellulose content of the CHF (58.40 ± 0.56 wt.%) provides better tensile strength 2013–2897 Mpa makes it an attractive option for synthetic fibers. FTIR and X-ray analysis proved that CHF is rich in cellulose content with crystallinity index (46.19%) and crystalline size (28.27 nm), which indicates that the CHF is thermally stable until 285.9°C. Moreover, the large crystalline sizes can reduce the water absorption characteristics. The strong presence of microfibril through scanning electron micrographs assists admirable bonding properties. The results are substantiating the potential of CHFs as reinforcement in composites industries with its significant possessions.